Dissenting Opinions Hakim Mahkamah Konstitusi Terhadap Pembatalan Peraturan Daerah Kabupaten/Kota Oleh Menteri Dalam Negeri Dikaitkan Dengan Pasal 24A Ayat (1) UUD 1945 (Putusan Mahkamah Konstitusi Nomor:137/PUU-XIII/2015) - Kantrey Sugiarto; Heru Drajat Sulistyo (Universitas Merdeka Madiun, 2019)
On April 4, 2017, the Panel of Judges of the Constitutional Court read out the decision on a judicial review of the laws of the Regional Government registered with case number 137 / PUU-XIII / 2015. Of the 9 (nine) judges who tried the case, there were 4 (four) judges who did dissenting opinions. With the Dissenting Opinion in this decision can be used as one of the quality parameters of the decision in fulfilling the sense of justice of the community, because it can be assessed the quality of thought of each judge and know the inner atmosphere that occurs during the judge deliberation meeting which is one of the crucial stages before a court ruling. The description of the activities carried out is, first to identify the facts of the law and to eliminate the irrelevant matters to establish legal issues to be solved. Second, collecting legal materials that are relevant to legal issues that are discussed so as to be able to solve these legal issues. Third, review legal issues submitted based on the materials collected. Fourth, draw conclusions in the form of arguments that answer legal issues. Fifth, provide text based on the arguments built in the conclusions.